Caesarean section in the second delivery to prevent anal incontinence after asymptomatic obstetric anal sphincter injury: the EPIC multicentre randomised trial. (6th September 2020) - Abramowitz, L; Mandelbrot, L; Bourgeois Moine, A; Tohic, AL; Carne Carnavalet, C; Poujade, O; Roy, C; Tubach, F
Abstract : Objective: To determine whether planned caesarean section (CS) for a second delivery protects against anal incontinence in women with obstetric anal sphincter lesions. Design: Randomised trial. Setting: Six maternity units in the Paris area. Sample: Women at high risk of sphincter lesions (first delivery with third‐degree laceration and/or forceps) but no symptomatic anal incontinence. Methods: Endoanal ultrasound was performed in the third trimester of the second pregnancy. Women with sphincter lesions were randomised to planned CS or vaginal delivery (VD). Main outcome measures: Anal incontinence at 6 months postpartum. Secondary outcomes were urinary incontinence, sexual morbidity, maternal and neonatal morbidities and worsening of external sphincter lesions. Results: Anal sphincter lesions were detected by ultrasound in 264/434 women enrolled (60.8%); 112 were randomised to planned VD and 110 to planned CS. At 6–8 weeks after delivery, there was no significant difference in anal continence between the two groups. At 6 months after delivery, median Vaizey scores of anal incontinence were 1 (interquartile range 0–4) in the CS group and 1 (interquartile range 0–3) in the VD group ( P = 0.34). There were no significant differences for urinary continence, sexual functions or for other maternal and neonatal morbidities. Conclusions: In women with asymptomatic obstetric anal sphincter lesions diagnosed by ultrasound, planning a CS had no significant impact on anal continence 6 months after the second delivery. These results do not support advising systematic CS for this indication. Tweetable abstract: Caesarean section for the second delivery did not protect against anal incontinence in women with asymptomatic obstetric anal sphincter lesions. Tweetable abstract: Caesarean section for the second delivery did not protect against anal incontinence in women with asymptomatic obstetric anal sphincter lesions.